Alterations in Cerebrospinal Fluid in Patients with Bipolar Syndromes - Endres, Dominique; Dersch, Rick; Hottenrott, Tilman; Perlov, Evgeniy; Maier, Simon; van Calker, Dietrich; Hochstuhl, Benedikt; Venhoff, Nils; Stich, Oliver; van Elst, Ludger Tebartz (Frontiers in Psychiatry, 2016)
Bipolar disorder (BD) is a severe and lifelong condition. Primary endogenic polygenetic forms are common. Secondary organic forms have received increasing interest recently due to the detection of immunological encephalopathies that mimic various psychiatric syndromes, including bipolar disorder. However, only limited data about routine findings of cerebrospinal fluid (CSF) analyses in bipolar disorder are available. Therefore, we investigated the frequency of alterations in the CSF in patients with BD and the association with autoantibodies, cerebral magnetic resonance imaging, and electroencephalography findings. CSF samples of patients with BD collected from January 1998 until December 2015 were analyzed retrospectively. Patients with preexisting causes for alterations in the CSF (e.g., patients with obvious past or current neurological disorders) were excluded. In total, 63 patients with BD fulfilled the inclusion criteria for the study. In 1.6% of the patients with BD, an increased white blood cell count was found in the CSF. Increased albumin quotients were found in 12.9% of the patients, oligoclonal bands (OCBs) in 1.6%, and increased immunoglobulin (Ig) G indices in 3.2% (OCBs were not measured in case of increased IgG indices). No significant differences in CSF findings were found between patients with manic and depressive episodes. The main findings of this open uncontrolled study are that alterations in the CSF may be found in a small but potentially relevant subgroup of patients with BD. These findings are discussed in light of the new concepts of mild encephalitis and immunological encephalopathy. The detection of patients with possibly secondary organic bipolar syndromes could open up new causal treatment options with immunomodulatory medication.